Fisher Ethnotaxonomy for Elasmobranchs Captured Along the Brazilian Amazon Coast - Coelho, Keyton K. F.; Rincon, Getulio; Marques Bandeira , Arkley; Vargas Barbosa Filho, Márcio Luiz; Wosnick, Natascha; Maria Serra de Brito, Rafaela; Onodera Palmeira Nunes, Ana Rita; Luiz Silva Nunes , Jorge (Ethnobiology Letters, 2023)
The diversity of popular names used in fish nomenclature off the Brazilian coast makes it difficult to identify species, and many names have their origins in Indigenous languages, mainly Tupi-Guarani. This study sought to understand and update the list of the most popular names and assess some ethnotaxonomic patterns employed by artisanal fishers from the Brazilian Amazon Coast in naming elasmobranchs. Interviews with 314 fishermen from 17 coastal municipalities were carried out employing a semi-structured form, banners, and photographic records of local elasmobranch species, addressing characteristics applied to species identification. A total of 130 ethnospecies were identified (113 names in Portuguese and 17 of Tupi-Guarani origin) for the identification of 22 and 18 species of sharks and rays, respectively. The highest degree of homonyms occurs interspecifically for the Dasyatidae, Mobulidae, Pristidae, Urotrygonidae, Carcharhinidae, Sphyrnidae and Triakidae families. Sphyrna tiburo and Hypanus guttatus comprised the taxa with the highest diversity of common names. Morphological characteristics such as shape, colors, texture, and size of certain body parts are the ethnotaxonomic patterns most applied in shark and ray identification. We conclude that the use of common names for elasmofauna facilitates communication between fishers and that the scientific approach to this local ecological knowledge is fundamental for the management and sustainability of fisheries in the long term.